A Quantitative Chronology of Diurnal Feeding in Juvenile Pacific Salmon. Issue 2 (4th March 2017) - Munsch, Stuart H.; Cordell, Jeffery R.; Toft, Jason D.
Abstract: Daily cycles in feeding intensity are common among fish and suggestive of ecological trade-offs and constraints. However, feeding chronologies are typically estimated from diets rather than in situ observations. As a consequence, our understanding of daily feeding patterns is often imprecise, which limits our ability to infer connections between these patterns and their drivers. Here we quantify in unprecedented temporal resolution the real-time diurnal feeding behavior of a fish assemblage. Snorkelers observed juvenile Pacific salmon Oncorhynchus spp. in estuarine waters between dawn and early evening. Fish fed throughout the day, with intake declining after dawn, and individuals allocated about 20% of their time to feeding at sunrise, declining to about 5% in the early evening. Many factors potentially influenced this behavior, including predation avoidance, physiological constraints, prey availability, and mandates for growth and migration. Prey mass in the stomachs of these fish increased shortly after dawn, reaching relatively stable levels through the afternoon. Thus, diet metrics detected the presence of feeding but not temporal changes in feeding intensity. Diets appear to provide limited information on the timing and intensity of feeding, and we may therefore only vaguely understand daily feeding patterns of fish when examining diets alone. Received June 17, 2016; accepted October 31, 2016 Published online January 19, 2017